Boosting project outcomes through goal alignment: a case study of Vietnam (Construction Economics and Building, 2014)
Goal alignment among members of a project team is important so that individual team members can work towards common project outcomes.  This study aims to identify effective goal alignment practices to improve construction project outcomes in Vietnam. With the aid of a survey questionnaire, data were collected from practitioners in Vietnam’s construction industry. The overall results show that although there is significant schedule overrun, projects in Vietnam are generally completed within budget.  These projects also have significantly good quality and client satisfaction.  The results show that goal alignment practices relating to having shared objectives, effective communication, flexibility, and fairness are significantly correlated with schedule performance, quality, and client satisfaction.  It is recommended that project team members share, align and adjust their goals and objectives in order to achieve a better schedule outcome.  Effective communication of problems pertaining to delivery and quality may lead to better client satisfaction.  It is also recommended that consultants and contractors make adjustments and customize their products to derive higher quality and client satisfaction.  Clients should also be fair in sharing project benefits and valuing variations.